Analisis Kepuasan Pelanggan Menggunakan Metode CSI dan STP untuk Meningkatkan Strategi Pemasaran pada UMKM BabonSenyum - Muhammad Thoriqul Haq; Yanuar Pandu Negoro; Hidayat Hidayat (Universitas Teuku Umar, 2023)
Milkfish is a popular food fish in Indonesia, more precisely in Gresik Regency there are many processed foods made from milkfish, one of which is Umkm BabonSenyum. Umkm Babonsenyum is a processed food business that is popular and often liked by a large number of people, both old people and young people. The problem that occurs in MSMEs is the lack of expanding promotions and increasing customer satisfaction. This research focuses on customer satisfaction in lower middle MSMEs, namely Babon Smile, one of the MSMEs located in Gresik Regency which produces shredded milkfish using the CSI (Customer Satisfaction Index) and STP (Segmenting Targeting Positioning) methods. and also uses data processing methods in the form of questionnaires, interviews and surveys from researchers. The results obtained from data processing using the CSI method show that customers are quite satisfied with the presentation of 60.68% and the results obtained from the STP method show that the products produced show 55% in terms of price, 55% in terms of location, 45% in terms of promotion. %, from these results it can be concluded that the strategy used obtained quite satisfactory results for AbonSenyum Umkm.